Sertraline as a rare cause of interstitial lung disease. Issue 4 (28th April 2021) - Lepore, Mario; Campbell, Niall
ABSTRACT: Sertraline, a selective serotonin reuptake inhibitor, is commonly prescribed for the treatment of moderate-to-severe depression. We report a case of a 36-year-old male taking sertraline for 7 weeks prior to developing a dry cough, pleuritic chest pain, hypoxia and diffuse ground-glass attenuation with mediastinal lymphadenopathy on imaging. No infectious aetiology was identified and multiple causes of pneumonitis excluded. Sertraline-induced interstitial lung disease was subsequently diagnosed. Sertraline was discontinued and treatment commenced with a weaning course of oral dexamethasone, leading to a rapid reduction in oxygen requirement and successful discharge. Given the increasing prevalence of selective serotonin reuptake inhibitor use, it is vital that medical professionals can recognize sertraline as a rare, albeit potentially life-threatening, cause of interstitial lung disease—allowing for the rapid diagnosis and appropriate management of this condition.